PRESERVING THE POSTHARVEST QUALITY OF THOMPSON SEEDLESS GRAPE BY USING PROPOLIS AND ALOE VERA GEL COATING - Ali Muhi Aldeen Omar Aljabary (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to save Thompson Seedless grapes and quality has been preserved through cold storage using an edible covering made from propolis and aloe vera gel. Thompson grapes have high value economically, but after they are picked, their shelf life is reduced due to a rapid decline in quality. Based on the rapid weight loss, low carotene content, softening, and frequent berry degradation, uncoated berries exhibited a rapid deterioration at 5°C and 85–90% relative humidity (RH). On the contrary, the above criteria relating to post-harvest quality losses were greatly delayed in those berries treated with propolis and aloe vera gel and may extend the storability up to 30 days at 5°C. Interestingly, weight loss, berries cracking, and decaying which greatly increased in uncoated berries throughout storage—were reduced by this edible coating. According to the author’s knowledge, propolis has never been used as an edible coating on grapes, which would be a novel and intriguing way for it to be used commercially and a substitute for the usage of chemical treatments during postharvest.